Assessing the economic impacts of food hubs on regional economies: a framework that includes opportunity cost - Jablonski, B. B. R., author; Schmit, T. M., author; Kay, D, author; Agricultural and Resource Economics Review, publisher (Colorado State University. Libraries, 2016)
The number of food hubs—businesses that aggregate and distribute local food—in the United States is growing, fueled in part by increasing public support. However, there have been few data-driven assessments of the economic impacts of these ventures. Using an input-output-based methodology and a unique data set from a successful food hub, we measure net and gross impacts of a policy supporting their development. We estimate a gross output multiplier of 1.75 and an employment multiplier of 2.14. Using customer surveys, we estimate that every $1 increase in final demand for food hub products generates a $0.11 reduction in purchases in other sectors.
Keywords: economic impact assessment; food hub; food policy; food systems; local food